Sediment Transport Pattern Modelling in Bojong Salawe Coast Pangandaran using Mike 21 - Nira Nirwana; Subiyanto Subiyanto; Yuniarti MS; Yudi Nurul Ihsan (International Journal of Quantitative Research and Modeling, 2021)
Bojong Salawe is a coastal area with unique characteristics due to a confluence of three rivers that flow through Cijulang, Cijalu, Cialit and into the Indian Ocean. With complex oceanographic conditions, the sediment transport patterns at Bojong Salawe needs to be contemplated, especially the coastal’s utilization which is quite productive. This study aims to determine the sediment types, the sediment transport patterns and the effect of sediment transport on abrasion or accretion which are supported by hydrodynamic parameters modelling such as wind, currents and tides in the west and east monsoons using hydrodynamic modules and sediment transport in MIKE 21. The results showed that the sediments in this study is 80% sandy silt and 20% sand. The sediment transport pattern models in both the west and east monsoons tend to be influenced by tidal currents, sediment types and the season itself. West monsoon has a higher sediment concentration which ranges from 0 to 8.4 kg/m3 compared to the East Monsoon with a range of 0-4 kg/m3. The effect of sediment transport on the average bed level was 0.71861 m in the west monsoon and 0.37586 m in the east monsoon whereas in the estuary (research station), the average change in West Monsoon is 0.00861 m (ST 1) and 0.07107 m (ST 2) and in the East Monsoon, it is 0.01003 m (ST 1) and 0.01147 m (ST 2). This bed level change tends to increase, indicating that the Bojong Salawe coast has experienced sedimentation (accretion).